2008
DOI: 10.1158/0008-5472.can-07-6469
|View full text |Cite
|
Sign up to set email alerts
|

Re-Expression of Transcription FactorATF5in Hepatocellular Carcinoma Induces G2-M Arrest

Abstract: Transcription factors represent an important class of genes that play key roles in controlling cellular proliferation, cell cycle modulation, and attractive targets for cancer therapy. Here, we report on the novel finding of common ATF5 downregulations in hepatocellular carcinoma (HCC), a highly malignant tumor with a dismal clinical course. Array-based mapping in HCC highlighted a high and consistent incidence of transcription factor ATF5 repressions on regional chr.19q13. By quantitative reverse transcriptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 39 publications
3
34
1
Order By: Relevance
“…These observations suggest that ATF5 may be an attractive target for therapeutic intervention in such tumor types. Consistent with these findings, ATF5 is highly expressed in a wide variety of neoplasms, including renal cell cancer, lung cancer, lymphomas, seminomas, cervical cancer, prostate cancer, hematopoietic carcinoma and hepatocellular carcinoma (17,20,25,26).…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…These observations suggest that ATF5 may be an attractive target for therapeutic intervention in such tumor types. Consistent with these findings, ATF5 is highly expressed in a wide variety of neoplasms, including renal cell cancer, lung cancer, lymphomas, seminomas, cervical cancer, prostate cancer, hematopoietic carcinoma and hepatocellular carcinoma (17,20,25,26).…”
Section: Introductionsupporting
confidence: 65%
“…Transcription factor ATF5, an ATF/CREB family member and bZIP protein, functions as a cancer-specific cell survival factor and promotes survival of cancer cells (22,32). Although evidence has been presented that ATF5 is involved in the onset and progression of cancer (20)(21)(22)(23)(24)(25)(26), no study, to the best of our knowledge, has reported whether ATF5 is related to rectal cancer. In the present study, the ATF5 protein and mRNA expression in human rectal carcinoma and normal tissue was analyzed using immunohistochemistry and RT-PCR.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, a query of the Oncomine cancer profiling database revealed that, in general, the expression level of ATF5 is significantly higher in malignant tissues than their normal counterpart tissues [11]. The only exception appears to be hepatocellular carcinoma cells, which express lower levels of ATF5 than normal liver cells; this discrepancy may be due to epigenetic silencing of ATF5 in hepatocellular carcinoma cells through promoter methylation [12]. Notably, increased levels of ATF5 have been observed in primary brain tumors, and ATF5 expression is particularly high in glioblastoma, an aggressive form of malignant glioma [10,11].…”
Section: Atf5 Expression In Cancermentioning
confidence: 99%
“…The activating transcription factor 5 (ATF5 or ATFx) is a member of the ATF/CREB transcription factor family. Although ATF5 is known to regulate cell cycle progression [4][5][6][7], cell survival [5][6][7][8][9][10][11][12][13], autophagy [14], cell fate determination [15][16][17] and cellular stress response [13][14][15][16][17][18][19], and it is likely involved in the development of schizophrenia [20][21][22] and chronic lymphocytic leukemia [23], only a few of its targets have been reported and the mechanism of ATF5 function remains largely unknown and occasionally controversial.Previous reports have shown that ATF5 enhances cell survival and proliferation of glioma, breast cancer cells and neuroprogenitor cells [5,[10][11][12]24] while eliciting a G2/M blockade in hepatocellular carcinoma cells [4,6]. ATF5 acts as a pro-survival factor in HeLa and hematopoietic FL5.12 cells [8] but may also increase cisplatin-induced apoptosis through up-regulation of cyclin D3 in HeLa cells [25].…”
mentioning
confidence: 99%